Siyasah tasyri’iyyah syar’iyyah - Firmansyah, Rio Ahmad (Maliki Interdisciplinary Journal, 2024)
After the leadership of al-Khulafa` al-Rashidin, Muslim state practice was characterized more as a centralized monarchy. Further developments in Islam were according to the dynasties of Bani Abbas from Bagdad to Ottoman Turkey in Istanbul. Then came Western colonialism, & Muslims attempted to adjust the pattern of interaction between faith & state. This was caused by western policies that sought to apply their political values to Islam. In this research, the author uses the library research method, which is a research activity that uses data collection & search and processing (books, literature & library materials) related to the topic of discussion. The type of research is qualitative research. Islam divides three powers, namely: Al-sulṭah altasyri`iyah is the power of the Islamic government to create & decide laws. Al-Sulṭah al-Tanfiẓiyyah is the power to enforce rules at the cabinet level of government. Al-Sullah Al-Qadiyah, on the other hand, is the duty & power of the judiciary, which is the power related to using the protection & supervision of the legislative process as an enforcer of rules. These three examples of power aim to avoid the concentration of power in a single ruler (authoritarian ruler).